2011
DOI: 10.1007/s00421-011-1936-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of energy expenditure on postprandial triacylglycerol in adolescent boys

Abstract: This study examined the effects of 30 and 60 min of moderate intensity exercise on postprandial triacylglycerol concentration [TAG] in 11 healthy, 13-year-old boys. The boys completed three counterbalanced conditions. On day 1, they either rested (CON), or jogged for 30 min (EX30) or 60 min (EX60) at 55% peak [Formula: see text] Following a 12-h fast, on day 2 a capillary blood sample was taken for fasting [TAG] before a high fat milkshake was consumed. Further blood samples were taken every hour over a 6-h po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

13
31
3

Year Published

2013
2013
2019
2019

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 20 publications
(47 citation statements)
references
References 37 publications
13
31
3
Order By: Relevance
“…In previous studies in adolescents, moderate-intensity exercise has been reported to reduce the total area under the plasma triacylglycerol concentrations versus time curve by 8 to 22% (Barrett et al, 2007;Lee et al, 2013;MacEneaney et al, 2009;Sedgwick et al, 2013;Tolfrey et al, 2008;Tolfrey et al, 2012) and high-intensity exercise (10 x 1 min run at 100% peak oxygen uptake) by 11% (Thackray, Barrett, & Tolfrey, 2013). In the present study the corresponding reduction was 13%, demonstrating that repeated bouts of very short (6 s) maximal sprints are effective at reducing postprandial triacylglycerol concentrations.…”
Section: Discussionsupporting
confidence: 60%
See 1 more Smart Citation
“…In previous studies in adolescents, moderate-intensity exercise has been reported to reduce the total area under the plasma triacylglycerol concentrations versus time curve by 8 to 22% (Barrett et al, 2007;Lee et al, 2013;MacEneaney et al, 2009;Sedgwick et al, 2013;Tolfrey et al, 2008;Tolfrey et al, 2012) and high-intensity exercise (10 x 1 min run at 100% peak oxygen uptake) by 11% (Thackray, Barrett, & Tolfrey, 2013). In the present study the corresponding reduction was 13%, demonstrating that repeated bouts of very short (6 s) maximal sprints are effective at reducing postprandial triacylglycerol concentrations.…”
Section: Discussionsupporting
confidence: 60%
“…A single 30 to 180 min session of moderate-intensity exercise completed 12 to 18 h prior to the ingestion of a high-fat meal has consistently been shown to lower postprandial triacylglycerol concentrations (Barrett, Morris, Stensel, & Nevill, 2006;Barrett, Morris, Stensel, & Nevill, 2007;Gill et al, 2004;Lee, Burns, Kuk, & Arslanian, 2013;MacEneaney et al, 2009;Petitt & Cureton, 2003;Sedgwick et al, 2013;Tolfrey et al, 2008;Tolfrey et al, 2012) and more recently to attenuate postprandial endothelial dysfunction in both adults and adolescents (Gill et al, 2004;Sedgwick et al, 2013;Tyldum et al, 2009). …”
Section: Introductionmentioning
confidence: 99%
“…A critical feature of the two-day model is that the exercise intervention precedes the first blood sample by 12 to 18 hours (Table 1). This is because lipoprotein lipase (LPL) activity appears to peak in this period after exercise (71) , it is likely the energy expenditure was lower than that reported in other studies in young people adopting longer and less intense exercise interventions (3,41,42,70,78,80,81), suggesting that exercise intensity is a key factor influencing postprandial TAG metabolism in young people. Importantly, the exercise protocol was well tolerated by the boys in this study, and recent evidence suggests that pre-pubertal boys prefer moderate intensity exercise interspersed with short bursts of high intensity effort compared with continuous moderate intensity exercise alone (9).…”
Section: Standardised Methods and Two-day Experimental Modelmentioning
confidence: 97%
“…While it appears that a 'threshold' of exercise energy expenditure may be required to promote a meaningful reduction in the postprandial TAG response, the evidence of a dose-dependent response is not yet supported directly in boys or girls (78,80,81).…”
Section: Implications and Future Directionsmentioning
confidence: 99%
See 1 more Smart Citation